Crime as deterrent to sustainable tourism growth? : perspectives on the impact of crime on tourism in the Western Cape - Dalhousie, Landi (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2005.